Five-in-one composite sulfur autotrophic denitrification filter material as well as preparation method and application thereof
Through five-in-one composite sulfur autotrophic denitrification filter and artificial wetland denitrification filter, combined with nano-modified graphene oxide and microelectrolysis technology, the low ammonia nitrogen removal efficiency and unbalanced carbon source consumption in wastewater are solved. The problem of low-cost and efficient deep nitrogen removal and environmentally friendly sewage treatment have been achieved.
Patent Information
- Application Number
- CN202411543706.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-13
AI Technical Summary
The existing technology has problems of low efficiency, high energy consumption and unbalanced carbon source consumption in the efficient removal of ammonia nitrogen in wastewater. The traditional biological nitrogen removal and phosphorus removal process cannot meet the requirements of efficient organic matter removal, especially during the denitrification process. There are shortcomings in source competition and environmental pollution.
Use five-in-one composite sulfur autotrophic denitrification filter, consisting of polyethylene glycol, polyvinyl alcohol, sodium alginate, sulfur autotrophic denitrification bacteria solution, elemental sulfur, activated carbon, sodium thiosulfate and calcium chloride , combined with nanomodified graphene oxide, calcium carbonate, pyrote, graphene oxide and nitrogen denitrogenation bacteria, we constructed artificial wetland-like denitrification deep nitrogen denitrogenation filtration with GO+ZVI+ slag carbon+high-efficiency nitrogen denitrogenation bacteria+photocatalytic artificial wetland denitrification deep nitrogen denitrogenation filtration Pool, photocatalysis and microelectrolysis technology to improve nitrogen removal effect.
It achieves low-cost and efficient deep nitrogen removal, reduces environmental pollution, solves the problems of low gel preservation and sulfur use efficiency in traditional technologies, and is suitable for large-scale industrial applications.
Smart Images

Figure CN119118359A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of denitrification filter material preparation, and particularly relates to a five-in-one composite sulfur autotrophic denitrification filter material and a preparation method and application thereof. Background Art
[0002] The current denitrification methods mainly include physical and chemical methods and biochemical denitrification methods. The principle of physical and chemical methods (evaporation, stripping, precipitation, membrane filtration, etc.) is to achieve deep denitrification by adsorbing, separating or converting ammonia nitrogen in sewage into other forms through physical, chemical or a combination of both methods. Conventional methods have low efficiency, high energy consumption and require the addition of carbon sources to achieve complete denitrification. Due to the unstable supply of nitrite, partial denitrification coupled with anaerobic ammonia oxidation (PD / A) limits the efficient removal of industrial ammonia nitrogen from wastewater. The differentiation of antioxidant capacity, microbial community transfer and metabolic flux redirection are the main reasons for this phenomenon. In conventional denitrification and phosphorus removal processes, the main causes of carbon source consumption are phosphorus release, denitrification and the normal metabolism of heterotrophic bacteria. The conventional biological nitrogen and phosphorus removal process has insufficient carbon source during the anoxic denitrification process, which affects the denitrification effect. However, for some improved processes, when the carbon source required for denitrification is prioritized, the system has poor P removal effect. A part of the carbon source in the anaerobic tank can be used as a carbon source for denitrification in a diverted manner, thus solving the problem of carbon source competition between phosphorus release and denitrification.
[0003] Tan Youming and Luo Qifang's research shows that immobilized microorganisms can effectively use glucose, sucrose, methanol, ethanol and acetic acid as added carbon sources for denitrification, especially glucose and acetic acid as added carbon sources for denitrification. In practical applications, immobilized microbial technology is mainly used, and the process system is further strengthened on this basis to make the effluent water quality better. However, the operating cost of the method of adding carbon sources is relatively high, which is too large for the funding pillar of medium and large sewage treatment plants, and is only suitable for small-scale wastewater treatment.
[0004] At present, with the increasingly serious water pollution problem in my country, people have higher and higher requirements for the removal of organic matter in sewage. The traditional biological denitrification and phosphorus removal process can no longer meet the treatment requirements and faces problems such as DPB enrichment and insufficient utilization. To this end, we provide a five-in-one composite sulfur autotrophic denitrification filter material and its preparation method and application to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to provide a five-in-one composite sulfur autotrophic denitrification filter material and a preparation method and application thereof. By developing a composite material based on nano-modified graphene oxide, a granular composite autotrophic denitrification filter material with photocatalytic properties is prepared using calcium carbonate material (egg shell), sulfur (or pyrite), graphene oxide (GO), and denitrification bacteria. Combined with zero-valent iron and sludge carbon micro-electrolysis materials, a GO+ZVI+sludge carbon+high-efficiency denitrification bacteria+photocatalytic five-in-one composite artificial wetland-like denitrification deep denitrification filter tank is constructed, which has low material cost and low environmental pollution.
[0006] In order to solve the above technical problems, the present invention is achieved through the following technical solutions: The invention discloses a five-in-one composite sulfur autotrophic denitrification filter material, which is composed of the following components: polyethylene glycol, polyvinyl alcohol, sodium alginate, water, sulfur autotrophic denitrification bacterial solution, elemental sulfur, activated carbon, sodium thiosulfate, calcium chloride and boric acid; the mass ratio of the polyethylene glycol, polyvinyl alcohol, sodium alginate, sulfur autotrophic denitrification bacterial solution, elemental sulfur, activated carbon and sodium thiosulfate is 0.1:50:1:50:10:10:15.
[0007] The above-mentioned sulfur autotrophic denitrification filter material is prepared by the following method: (1) Use an electronic balance to accurately weigh a certain amount of polyethylene glycol, polyvinyl alcohol and sodium alginate, mix the polyethylene glycol, polyvinyl alcohol and sodium alginate with 10 mL of ultrapure water, and heat them in a 50°C water bath to dissolve. After stirring for a period of time, a gel is obtained and the temperature is cooled to 25°C. (2) accurately weighing a certain amount of sulfur autotrophic denitrifying bacteria liquid, elemental sulfur, activated carbon and sodium thiosulfate, and uniformly mixing the weighed sulfur autotrophic denitrifying bacteria liquid, elemental sulfur, activated carbon and sodium thiosulfate with the gel in the above step (1) to obtain a mixed solution; (3) The mixed solution obtained in the above step (2) is dripped into a mixed solution of 1% calcium chloride and 50% boric acid, and allowed to stand for 18 hours for a cross-linking reaction. After the cross-linking reaction, immobilized microspheres are obtained. The immobilized microspheres are then washed several times with ultrapure water to obtain a sulfur autotrophic denitrification filter material.
[0008] The present invention is further preferably, using sulfur autotrophic denitrification filter material as filler to construct a denitrification reactor based on GO+ZVI+sludge carbon+high-efficiency denitrification bacteria+photocatalysis, wherein the denitrification reactor consists of a simulated vertical flow wetland denitrification filter and a photocatalytic lamp located in the center of the filter; the simulated vertical flow wetland denitrification filter is provided with a filler layer, a supporting layer and an aeration backwashing device from top to bottom, and a backwashing pump is provided below the filler layer for backwashing the filler layer, and the water inlet mode of the simulated vertical flow wetland denitrification filter is top-in and bottom-out.
[0009] The present invention is further preferred that the packing layer comprises pyrite unfired ceramsite and a granular composite filter material; wherein the pyrite unfired ceramsite is prepared from pyrite tailings, cement, quicklime, gypsum, dry sludge and sodium bicarbonate, and the mass ratio of the pyrite tailings, cement, quicklime, gypsum, dry sludge and sodium bicarbonate is 42.25:10:0.5:0.5:1.5:0.25; the granular composite filter material is prepared from sulfur, eggshell and graphene oxide, and the mass ratio of the sulfur, eggshell and graphene oxide is 275.2:500:1.
[0010] The present invention is further preferably that the filler layer comprises an amino-modified graphene oxide gel, which is prepared by the following method: (1) Weigh 75 mg of graphene oxide fluffy body and place it in a 50 mL polyethylene centrifuge tube. Add 30 mL of ultrapure water and seal it and suspend it in an ultrasonic cleaner. Add the brown-yellow solution obtained after ultrasonic treatment evenly into three 25 mL weighing bottles. (2) Weigh 13 mg of titanium dioxide into each weighing bottle, then place each weighing bottle on a magnetic stirrer, stir at 350 r / min for 15 min, and measure the pH value to be 2.6-2.8; (3) Weigh 0.76 mg of indium nitrate tetrahydrate into each weighing bottle, then place each weighing bottle on a magnetic stirrer and stir at 350 r / min for 15 min; (4) Quickly add 1 mL of ethylenediamine to each weighing bottle using a pipette. The solution in the weighing bottle immediately turns blue-black. The pH value of the solution is 10.5. Stir at 350 r / min for 10 min and then ultrasonicate for 10 min. (5) The solutions in each weighing bottle were transferred to a 25 mL polytetrachloroethylene reactor, sealed with a stainless steel jacket, and heated in the reactor. When the temperature reached 180°C, the reaction was kept warm for 12 h. After the reaction was completed, the reactor was taken out and opened after naturally cooling to room temperature. A three-dimensional cylindrical solid hydrogel was precipitated at the bottom of the solution. (6) The three-dimensional cylindrical solid hydrogel was rinsed with ultrapure water for several times, sealed and placed in a -80°C refrigerator for 24 h. After freezing, it was placed in a freeze dryer for lyophilization for 36 h to obtain a three-dimensional porous graphene / titanium dioxide / indium nitrate nanospindle aerogel.
[0011] The present invention is further preferably that the filler layer comprises an amino-modified graphene oxide gel, which is prepared by the following method: (1) Weigh 75 mg of graphene oxide fluffy body and place it in a 50 mL polyethylene centrifuge tube. Add 30 mL of ultrapure water and seal it and suspend it in an ultrasonic cleaner. Add the brown-yellow solution obtained after ultrasonic treatment evenly into three 25 mL weighing bottles. (2) Weigh 13 mg of titanium dioxide into each weighing bottle, then place each weighing bottle on a magnetic stirrer, stir at 350 r / min for 15 min, and measure the pH value to be 2.6-2.8; (3) Weigh 5 mg of carbon nitride into each weighing bottle, then place each weighing bottle on a magnetic stirrer and stir at 350 r / min for 15 min; (4) Quickly add 1 mL of ethylenediamine to each weighing bottle using a pipette. The solution in the weighing bottle immediately turns blue-black. The pH value of the solution is 10.5. Stir at 350 r / min for 10 min and then ultrasonicate for 10 min. (5) The solutions in each weighing bottle were transferred to a 25 mL polytetrachloroethylene reactor, sealed with a stainless steel jacket, and heated in the reactor. When the temperature reached 180°C, the reaction was kept warm for 12 h. After the reaction was completed, the reactor was taken out and opened after naturally cooling to room temperature. A three-dimensional cylindrical solid hydrogel was precipitated at the bottom of the solution. (6) The three-dimensional cylindrical solid hydrogel was rinsed with ultrapure water for several times, sealed and placed in a -80°C refrigerator for 24 h. After freezing, it was placed in a freeze dryer for 36 h to obtain a three-dimensional porous graphene / titanium dioxide / carbon nitride nanospindle aerogel.
[0012] The present invention is further preferably that the graphene oxide in the preparation process of the above-mentioned amino-modified graphene oxide gel is prepared by the following method: (1) Using anaerobic fermentation residue as raw material, the biochar was graphitized by 1.0% B + 6.0% Fe combined catalysis to obtain graphite products; (2) Place the bio-ice bag in a constant temperature water bath, measure 130 mL of concentrated sulfuric acid and place it in a 500 mL three-necked flask, accurately weigh 5 g of graphite prepared from biogas residue and 2.5 g of sodium nitrate, add them to the concentrated sulfuric acid, and react in an ice bath for 2 h; (3) Slowly add 15 g of potassium permanganate and continue stirring in an ice bath for 2 h. After the reaction is complete, remove the ice bath and transfer the three-necked flask to a 35°C water bath and continue stirring for 1 h. (4) Slowly add 230 mL of deionized water to the three-necked flask and heat the water bath to 98 °C. Continue the reaction at this temperature for 30 min after the water is added. After removing the water bath, transfer the solution to a 1000 mL beaker and slowly add 400 mL of deionized water and 10 mL of hydrogen peroxide. Continue stirring and reacting for 1 h. (5) Pour the solution after the reaction into a centrifuge tube and centrifuge for 5 min. After discarding the supernatant, use 7% hydrochloric acid solution to centrifuge and wash several times at the same speed to remove metal ions and sulfate ions in the solution. After washing, use barium chloride solution to check whether all sulfate ions have been removed. Then wash several times with deionized water until the pH is 6.95-7.05. Finally, pour the cleaned sample into an evaporating dish and put it into a freeze dryer for drying. After drying, use a grinder to grind it into powder.
[0013] The present invention is further preferred that the filler layer includes nano-zero-valent iron-loaded graphene oxide, which is prepared by the following method: the prepared nano-zero-valent iron and graphene oxide are ground in a mortar in a mass ratio of 1:1, and then a certain amount of anhydrous ethanol and polyvinyl pyrrolidone dispersant are added, and the mixture is broken into a sol and recombined by ultrasound for 10 minutes, and the pH is adjusted and reacted for a period of time. After the reaction is completed, it is transferred to a vacuum drying oven and dried for 12 hours to obtain nano-zero-valent iron-loaded graphene oxide.
[0014] The present invention is further preferred that the filler layer includes biogas residue activated carbon, which is prepared by the following method: using kitchen biogas residue as raw material, filtering the biogas residue, drying it and crushing it into uniform powder; placing the powdered biogas residue in a porcelain boat and pushing it into a pyrolysis steel tube furnace of a tubular resistance furnace, introducing nitrogen and keeping it warm at a pyrolysis temperature of 1000°C for 5 hours; after the procedure is completed, taking out the high-temperature resistant porcelain boat after naturally cooling to room temperature, collecting the black powder to obtain biogas residue activated carbon with a graphene structure.
[0015] The present invention has the following beneficial effects: The present invention develops a composite material based on nano-modified graphene oxide, adopts calcium carbonate material, pyrite, graphene oxide, and denitrifying bacteria to prepare a granular composite autotrophic denitrification filter material with photocatalytic properties, combines zero-valent iron and sludge carbon micro-electrolysis materials, and constructs a GO+ZVI+sludge carbon+high-efficiency denitrifying bacteria+photocatalytic five-in-one composite artificial wetland-like denitrification deep denitrification filter tank, which has low material cost and low environmental pollution. At the same time, the present invention solves the problem that gel is used in the existing preparation technology but cannot be preserved for a long time and is not suitable for large-scale industrial applications. At the same time, the present invention adopts the technology of mixed use of sulfur and ferrous sulfide, which solves the problem that the denitrification effect is low and a large amount of sulfate will be generated due to the use of sulfur alone.
[0016] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0018] Figure 1 This is the degradation diagram of nitrate nitrogen concentration of different filter media.
[0019] Figure 2 This is the degradation diagram of nitrite nitrogen concentration of different filter materials.
[0020] Figure 3 This is the degradation diagram of ammonia nitrogen concentration of different filter materials.
[0021] Figure 4 This is the total nitrogen concentration degradation diagram of different filter media.
[0022] Figure 5 This is a comparison chart of the removal rates of nitrate nitrogen, ammonia nitrogen and total nitrogen in static experiments.
[0023] Figure 6 This is a trend chart of total nitrogen (A) and nitrate nitrogen (B) concentration changes in the dynamic experiment of iron-carbon micro-electrolysis attached filter material. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1 Filter material preparation A pyrite tailings unburned ceramsite is prepared using pyrite tailings, cement, quicklime, gypsum, dry sludge, and sodium bicarbonate as raw materials; a granular composite filter material is prepared using sulfur, egg shells, and graphene oxide as raw materials; a sulfur autotrophic denitrification filter material particle (biologically active particle) is prepared using polyethylene glycol, polyvinyl alcohol, sodium alginate, water, sulfur autotrophic denitrification bacteria liquid, elemental sulfur, activated carbon, sodium thiosulfate, calcium chloride, and boric acid. The above-mentioned sulfur autotrophic denitrification filter material is prepared by the following method:
[0026] (1) Mix polyethylene glycol, polyvinyl alcohol and sodium alginate with 10 mL of ultrapure water and heat in a water bath set at 50°C to dissolve. Stir to obtain a gel and cool to 25°C.
[0027] (2) The sulfur autotrophic denitrifying bacteria liquid, elemental sulfur, activated carbon, sodium thiosulfate and the gel prepared in the above step (1) are uniformly mixed to obtain a mixed liquid.
[0028] (3) The mixed solution prepared in the above (2) was dropped into a mixed solution of 1% calcium chloride and 50% boric acid, and allowed to stand for 18 hours for a cross-linking reaction. The immobilized microspheres obtained after the cross-linking reaction were washed several times with ultrapure water to finally obtain a sulfur autotrophic denitrification filter material.
[0029] The preparation materials of pyrite tailings unburned ceramsite (per 55g raw material) are shown in Table 1.
[0030] Table 1 Content of unburned ceramsite in pyrite tailings 55g of raw materials, including sulfur (or iron sulfide), cement, quicklime, gypsum, dry sludge and sodium bicarbonate in the proportions of Table 1, were mixed evenly with 12.5mL of water, and the fluffy mixed powder was poured into a blender to roll it to form spherical particles. Particles of different sizes were screened out with a powder sieve, and particles with small sizes could continue to be put into the blender and rolled, and finally particles with a particle size of ≥5mm were obtained. The particles of appropriate size were air-dried for 2h under natural conditions, and then placed in a 100℃ autoclave for steam curing for 15min. After the temperature of the autoclave dropped below 30℃, the autoclave was opened and taken out, and water was sprayed regularly for curing for at least 2 days to finally obtain pyrite tailings unburned ceramsite.
[0031] The mass ratios of various components in the above-mentioned granular composite filter material are shown in Table 2.
[0032] Table 2 Mass ratio of each component of granular composite filter material The contents of various components in the above sulfur autotrophic denitrification filter material are shown in Table 3.
[0033] Table 3 Content of each component of sulfur autotrophic denitrification filter material (prepared according to 100 mL ultrapure water) Example 2 Construction of GO+ZVI+biogas residue carbon+high-efficiency denitrification bacteria+photocatalysis five-in-one composite artificial wetland-like denitrification deep denitrification filter (1) Preparation of graphene oxide (GO) First, graphene oxide is prepared, and the preparation is divided into five stages: pre-oxidation, low-temperature reaction, medium-temperature reaction, high-temperature reaction stage, and washing and drying stage.
[0034] Pre-oxidation stage: put the biological ice bag into a constant temperature water bath, measure 130 mL of concentrated sulfuric acid and put it into a 500 mL three-necked flask, accurately weigh 5 g of natural flake graphite and 2.5 g of sodium nitrate and add them to the concentrated sulfuric acid, and react in an ice bath for 2 h; Low temperature reaction stage: After the pre-oxidation is completed, slowly add 15 g of potassium permanganate and continue stirring the reaction in an ice bath for 2 h; Medium temperature reaction stage: remove the ice bath, transfer the three-necked flask to a 35°C water bath and continue stirring the reaction for 1 h; High temperature reaction stage: slowly add 230 mL of deionized water to the three-necked flask, and heat the water bath to 98°C. After adding water, continue the reaction at this temperature for 30 min. Remove the water bath, transfer the solution to a 1000 mL beaker, slowly add 400 mL of deionized water and 10 mL of hydrogen peroxide, and stir for 1 h before the reaction ends. Washing and drying stage: pour the reaction solution into a centrifuge tube and centrifuge (8000r / min) for 5 min, then pour out the supernatant, prepare 7% hydrochloric acid (freshly prepared), stir thoroughly, and centrifuge and wash several times at the same speed to remove metal ions and sulfate ions in the solution. After washing, use barium chloride solution to detect whether all sulfate ions have been removed; then wash several times with deionized water using the same method until the pH is close to 6.95-7.05; then pour the washed sample into an evaporating dish, put it into a freeze dryer for drying, and then grind it into powder with a grinder after drying.
[0035] Experiment on preparing graphene oxide from biochar: In order to reduce costs, cheap biochar (anaerobic fermentation residue) was used as raw material, and 1.0% B + 6.0% Fe was jointly catalyzed to promote the graphitization of biochar to obtain graphite products, and then graphene oxide was prepared according to the above method to reduce costs and realize resource utilization.
[0036] (2) Preparation of amino-modified graphene oxide gel Different reducing agents, including amino materials such as ethylenediamine and tripolynitrile amine, were used as reducing agents for amino functionalization. At the same time, materials such as carbon nitride and titanium dioxide were introduced to give the materials photocatalytic activity. The adsorption and removal performance of different materials was investigated to obtain a series of graphene oxide gel materials with high removal efficiency. Among them, the preparation scheme of three-dimensional porous graphene / titanium dioxide / indium nitrate nanospindle aerogel is as follows:
[0037] 75 mg of graphene oxide fluffy body was placed in a 50 mL polyethylene centrifuge tube, 30 mL of ultrapure water was added, and the tube was sealed and suspended in an ultrasonic cleaner. The brown-yellow solution was then evenly added to three 25 mL weighing bottles.
[0038] Weigh 13 mg of titanium dioxide into one of the weighing bottles, and do the same for the other two weighing bottles. Stir it with a magnetic stirrer at 350 rpm for 15 min. Measure its pH to be 2.6-2.8.
[0039] Weigh 0.76 mg of indium nitrate tetrahydrate into one of the weighing bottles, and do the same for the other two weighing bottles. Stir them with a magnetic stirrer at 350 rpm for 15 min.
[0040] Then use a pipette to quickly inject 1 mL of ethylenediamine (EDA) into the weighing bottle. The solution immediately turns blue-black and its pH is measured to be 10.5. Continue stirring on a magnetic stirrer at 350 rpm for 10 min, and then place it in ultrasound for 10 min.
[0041] Then transfer the entire solution in the weighing bottle to a 25 mL polytetrachloroethylene reactor, seal it with a stainless steel jacket and place it in the reactor to heat. When the temperature reaches 180°C, keep the reaction at this temperature for 12 hours. After the reaction is completed, turn off the power of the reactor. After it cools naturally to room temperature, take out the reactor and open it. You can see the three-dimensional cylindrical solid hydrogel precipitated at the bottom of the solution.
[0042] It was rinsed with ultrapure water several times, sealed and placed in a -80°C medical refrigerator for 24 h, and then placed in a freeze dryer for lyophilization for 36 h to obtain a three-dimensional TiO2 / AGO / In nanospindle aerogel.
[0043] The preparation of three-dimensional porous graphene / titanium dioxide / carbon nitride nanospindle aerogel is similar to the above, except that 0.76 mg of indium nitrate tetrahydrate is replaced with 5 mg of carbon nitride.
[0044] (3) Nano-zero-valent iron loaded graphene oxide (Fe 0 Preparation of GO The prepared nano zero-valent iron (nZVI) and graphene oxide (GO) were ground in a mortar at a mass ratio of 1:1, and then a certain amount of anhydrous ethanol and polyvinyl pyrrolidone dispersant were added. The mixture was crushed into a sol and reorganized by ultrasound for 10 min, the pH was adjusted, and then after a reaction period, it was transferred to a vacuum drying oven and dried for 12 h to obtain nano zero-valent iron loaded graphene oxide (Fe 0 / GO).
[0045] (4) Preparation of activated carbon from biogas residue Using kitchen sludge as raw material, the sludge is filtered, dried and crushed into uniform powder; the powdered sludge is placed in a porcelain boat and pushed into the pyrolysis steel tube furnace of a tubular resistance furnace, and after nitrogen is introduced, it is maintained at a pyrolysis temperature of 1000°C for 5 hours; after the program is completed, the high-temperature resistant porcelain boat is taken out after naturally cooling to room temperature, and the black powder, namely graphene, is collected.
[0046] (5) Photocatalytic denitrification equipment design Construct a photocatalytic denitrification reactor, which consists of a denitrification filter tank and a photocatalytic lamp located in the center of the filter tank. The operation mode adopts upflow water inlet, aeration backwashing by a blower, and regular water washing by a backwashing pump. The filter tank water enters from the top and exits from the bottom. From top to bottom, it is the packing layer, the supporting layer, and the aeration device. Regular backwashing is required to remove the aging biofilm on the surface of the filter stone. The packing layer is composed of sand and gravel of different particle sizes, graphene oxide, iron, carbon and other materials, and the upper layer is the reaction zone.
[0047] The present application designs a five-in-one denitrification filter tank that simulates a vertical flow wetland. The five-in-one includes GO+ZVI+sludge carbon+high-efficiency denitrification bacteria+photocatalytic new technology that reinforce each other. Microorganisms are inoculated on carriers such as iron, carbon, and sand and gravel, and the denitrification effect is enhanced by using the iron-carbon micro-electrolysis reduction effect and the electronic conduction effect of GO+photocatalysis.
[0048] (6) Screening and cultivation of denitrifying bacteria Paracoccus denitrifying can be used alone or in combination with a carrier to form a microbial agent. The removal rate of nitrate-nitrogen in high-salinity wastewater is higher than 95%. It can effectively improve the biological treatment effect of nitrate-nitrogen in high-salinity water bodies. At the same time, it can further improve the denitrification efficiency and operational stability of sewage treatment facilities under high-salinity extreme environmental conditions. It has broad application prospects and value. The bacteria denitrify wastewater through a sulfur-iron co-substrate autotrophic process, which has the advantages of low energy consumption, simple process, and less sludge. However, in actual applications, microbial activities are easily affected by environmental conditions such as shock loads and heavy metal stress, making the effluent unstable. This application intends to use Paracoccus denitrifying to culture in advance, and then screen for efficient engineering bacteria for denitrification of food biogas slurry for engineering application.
[0049] Activate Paracoccus denitrificans under anaerobic conditions, inject about 0.3-0.5 mL of sterile water or liquid culture medium into the freeze-dried tube, blow gently to fully dissolve into bacterial suspension. Pipette the bacterial suspension, evenly inject it into the surface of 2 agar plates (about 200uL / plate), spread it evenly, and culture it at 30℃. The first activation prohibits streaking. After successful activation, relevant tests can be carried out, and after activation, it can be subcultured.
[0050] Example 3 Water treatment parameter optimization This application first uses simulated sewage treatment plant wastewater for startup experiments. By adding potassium nitrate to deionized water, synthetic wastewater contaminated with nitrate is prepared. The nitrate nitrogen concentration of the prepared solution is about 50 mg / L. The sludge microorganisms are domesticated for 2 months. The next step can be carried out only after the microorganisms in the sludge are stable.
[0051] First, artificial domestication and cultivation are used to enable the denitrifying bacteria to achieve excellent denitrification effects, thereby obtaining excellent domesticated strains; after more than two months of domestication, their own anti-interference ability and adaptability to the surrounding environment help to improve the denitrification efficiency, and the cultivated sludge is black-brown flocculent.
[0052] In practical applications, microbial activities are easily affected by environmental conditions such as impact loads and heavy metal stress, which makes the effluent unstable. This application intends to use denitrifying Paracoccus for preliminary cultivation, and then screen high-efficiency engineered bacteria for denitrification of food waste liquid for engineering application.
[0053] The denitrification filter media static experiment bottles 1-8 are shown in Table 4.
[0054] Table 4 Denitrification filter static test serial number table According to the above table, an experiment was conducted to explore the denitrification performance of the denitrification filter material. The water sample concentrations were measured at 12 h, 24 h, 36 h, 48 h, 72 h and 84 h. The specific denitrification effect is shown in the attached Figure 1-Figure 5 As shown in the figure (where SE stands for aminated graphene oxide and SEGO stands for graphene oxide). Bottles 2-8 can reduce the concentration of nitrate nitrogen. The concentration of nitrate nitrogen drops precipitously from 24 h to 36 h, and the degradation rate is the fastest. After 36 h, the conversion of nitrate nitrogen is basically completed. However, the denitrification with the composite filter material is more complete. The removal rate of nitrate nitrogen with the composite filter material and denitrifying bacteria is more than 95%, proving that the sulfur autotrophic composite filter material has a removal effect.
[0055] Nitrite nitrogen is an intermediate produced in the denitrification process. The concentration of nitrite nitrogen gradually increased within 0-36 h, resulting in nitrite nitrogen accumulation, and then gradually disappeared, which is consistent with the denitrification process. In general, the addition of 0.3g of graphene oxide to the 1.72:1 S:eggshell composite material has a promoting effect on the removal of nitrate nitrogen and total nitrogen.
[0056] In this application, iron-carbon micro-electrolysis was also added to the denitrification filter. The kitchen wastewater was added to the simulated denitrification filter and the timing was started. Water samples were taken after 1 h, 2 h, 4 h, 7 h, 11 h, and 24 h. Since the simulated denitrification filter was small and the amount of water treated was small, the water samples were diluted 20 times with ultrapure water. The denitrification effect of the water samples is shown in Table 5, and the trend of the total nitrogen concentration and the trend of the nitrate nitrogen concentration are shown in Table 5. Figure 6 shown.
[0057] Table 5 Dynamic experimental denitrification effect of iron-carbon micro-electrolysis adsorption filter material according to Figure 6 The results show that the biofilm filter material can remove 100% of nitrate nitrogen within 0.5 hours of the experiment during denitrification, and the total nitrogen removal efficiency is 39%. When the reaction lasts for 24 hours, the total nitrogen removal rate is 63%.
[0058] The composite filter material in this application is composed of three materials, including sulfur autotrophic ceramsite, sulfur autotrophic denitrification granular filter material, and the third is sulfur autotrophic denitrification active filter material. The main difference between granular filter material and ceramsite is the particle size, which allows the ceramsite (particle size 3-5mm) to be at the bottom and the particles (particle size 1-3mm) to be on top. The sulfur autotrophic denitrification active filter material is doped with denitrifying bacteria, which has the function of supplementing active bacteria.
[0059] Vertical flow artificial wetland refers to a wetland that uses bottom-up flow and plants on top to simulate artificial wetlands. Plants absorb nitrogen and phosphorus in the water through growth, and nitrogen and phosphorus are transferred from the water to the organic phase by regular harvesting of plants.
[0060] The micro-battery system composed of valent iron and sludge carbon can realize the auxiliary reduction of nitrate nitrogen in the water. The 680nm yellow light system is used to enhance the denitrification effect. Compared with not using the yellow light system, the denitrification efficiency can be increased by 12-38%. A five-in-one composite artificial wetland-like denitrification deep denitrification filter tank of GO+ZVI+sludge carbon+high-efficiency denitrification bacteria+photocatalysis is constructed, with low material cost and little environmental pollution.
[0061] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0062] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A five-in-one composite sulfur autotrophic denitrification filter material, characterized in that: The sulfur autotrophic denitrification filter material is composed of the following components: Polyethylene glycol, polyvinyl alcohol, sodium alginate, water, sulfur autotrophic denitrifying bacteria solution, elemental sulfur, activated carbon, sodium thiosulfate; The above-mentioned sulfur autotrophic denitrification filter material is prepared by the following method: (1) Use an electronic balance to accurately weigh a certain amount of polyethylene glycol, polyvinyl alcohol and sodium alginate, mix the polyethylene glycol, polyvinyl alcohol and sodium alginate with 10 mL of ultrapure water, and heat them in a 50°C water bath to dissolve. After stirring for a period of time, a gel is obtained and the temperature is cooled to 25°C. (2) accurately weighing a certain amount of sulfur autotrophic denitrifying bacteria liquid, elemental sulfur, biogas residue activated carbon and sodium thiosulfate, and uniformly mixing the weighed sulfur autotrophic denitrifying bacteria liquid, elemental sulfur, biogas residue activated carbon and sodium thiosulfate with the gel in the above step (1) to obtain a mixed solution; (3) The mixed solution obtained in the above step (2) is dripped into a mixed solution of 1% calcium chloride and 50% boric acid, and allowed to stand for 18 hours for a cross-linking reaction. After the cross-linking reaction, immobilized microspheres are obtained. The immobilized microspheres are then washed several times with ultrapure water to obtain a sulfur autotrophic denitrification filter material.
2. A five-in-one composite sulfur autotrophic denitrification filter material according to claim 1, characterized in that: The mass ratio of the polyethylene glycol, polyvinyl alcohol, sodium alginate, sulfur autotrophic denitrifying bacteria liquid, elemental sulfur, activated carbon and sodium thiosulfate is 0.1:50:1:50:10:10:
15.
3. An application of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 2, characterized in that: A denitrification reactor based on GO+ZVI+sludge carbon+high-efficiency denitrification bacteria+photocatalysis is constructed by using sulfur autotrophic denitrification filter material as filler. The denitrification reactor consists of a simulated vertical flow wetland denitrification filter and a photocatalytic lamp located in the center of the filter. The simulated vertical flow wetland denitrification filter is provided with a filler layer, a supporting layer and an aeration device from top to bottom, and a backwash pump is provided below the filler layer for backwashing the filler layer. The water inlet mode of the simulated vertical flow wetland denitrification filter is top-in and bottom-out.
4. The use of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 3, characterized in that: The packing layer includes pyrite unfired ceramsite and granular composite filter material; wherein the pyrite unfired ceramsite is prepared from pyrite tailings, cement, quicklime, gypsum, dry sludge and sodium bicarbonate, and the mass ratio of the pyrite tailings, cement, quicklime, gypsum, dry sludge and sodium bicarbonate is 42.25:10:0.5:0.5:1.5:0.25; the granular composite filter material is prepared from sulfur, eggshell and graphene oxide, and the mass ratio of the sulfur, eggshell and graphene oxide is 275.2:500:
1.
5. The use of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 4, characterized in that: The filler layer includes an amino-modified graphene oxide gel, which is prepared by the following method: (8) Weigh 75 mg of graphene oxide fluffy body and place it in a 50 mL polyethylene centrifuge tube. Add 30 mL of ultrapure water and seal it and suspend it in an ultrasonic cleaner. Add the brown-yellow solution obtained after ultrasonic treatment evenly into three 25 mL weighing bottles. (9) Weigh 13 mg of titanium dioxide into each weighing bottle, then place each weighing bottle on a magnetic stirrer, stir at 350 r / min for 15 min, and measure the pH value to be 2.6-2.8; (10) Weigh 0.76 mg of indium nitrate tetrahydrate into each weighing bottle, then place each weighing bottle on a magnetic stirrer and stir at 350 r / min for 15 min; (11) Quickly add 1 mL of ethylenediamine to each weighing bottle using a pipette. The solution in the weighing bottle immediately turns blue-black. The pH value of the solution is 10.
5. Stir at 350 r / min for 10 min and then ultrasonicate for 10 min. (12) The solutions in each weighing bottle were transferred to a 25 mL polytetrachloroethylene reactor, sealed with a stainless steel jacket, and heated in the reactor. When the temperature reached 180 °C, the reaction was kept warm for 12 h. After the reaction was completed, the reactor was taken out and opened after naturally cooling to room temperature. A three-dimensional cylindrical solid hydrogel was precipitated at the bottom of the solution. (13) The three-dimensional cylindrical solid hydrogel was rinsed several times with ultrapure water, sealed and placed in a -80 °C refrigerator for 24 h. After freezing, it was placed in a freeze dryer for 36 h to obtain a three-dimensional porous graphene / titanium dioxide / indium nitrate nanospindle aerogel.
6. The use of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 4, characterized in that: The filler layer includes an amino-modified graphene oxide gel, which is prepared by the following method: (15) Weigh 75 mg of graphene oxide fluffy body and place it in a 50 mL polyethylene centrifuge tube. Add 30 mL of ultrapure water and seal it and suspend it in an ultrasonic cleaner. Add the brown-yellow solution obtained after ultrasonic treatment evenly into three 25 mL weighing bottles. (16) Weigh 13 mg of titanium dioxide into each weighing bottle, then place each weighing bottle on a magnetic stirrer and stir at 350 r / min for 15 min. Then measure the pH value to be 2.6-2.
8. (17) Weigh 5 mg of carbon nitride into each weighing bottle, then place each weighing bottle on a magnetic stirrer and stir at 350 r / min for 15 min; (18) 1 mL of ethylenediamine was quickly added to each weighing bottle using a pipette. The solution in the weighing bottle immediately turned blue-black. The pH of the solution was measured to be 10.
5. The mixture was stirred at 350 r / min for 10 min and then ultrasonically treated for 10 min. (19) The solutions in each weighing bottle were transferred to a 25 mL polytetrachloroethylene reactor, sealed with a stainless steel jacket, and heated in the reactor. When the temperature reached 180 °C, the reaction was kept warm for 12 h. After the reaction was completed, the reactor was taken out and opened after naturally cooling to room temperature. A three-dimensional cylindrical solid hydrogel was precipitated at the bottom of the solution. (20) The three-dimensional cylindrical solid hydrogel was rinsed several times with ultrapure water, sealed and placed in a −80 °C refrigerator for 24 h. After freezing, it was placed in a freeze dryer for 36 h to obtain a three-dimensional porous graphene / titanium dioxide / carbon nitride nanospindle aerogel.
7. The use of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 5 or 6, characterized in that: The graphene oxide is prepared by the following method: (22) Using anaerobic fermentation residue as raw material, the biochar was graphitized by 1.0% B + 6.0% Fe combined catalysis to obtain graphite products; (23) Place the biological ice bag in a constant temperature water bath, measure 130 mL of concentrated sulfuric acid and place it in a 500 mL three-necked flask, accurately weigh 5 g of graphite prepared from biogas residue and 2.5 g of sodium nitrate and add them to the concentrated sulfuric acid, and react in an ice bath for 2 h; (24) Slowly add 15 g of potassium permanganate and continue stirring in an ice bath for 2 h. After the reaction is complete, remove the ice bath and transfer the flask to a 35 °C water bath and continue stirring for 1 h. (25) Slowly add 230 mL of deionized water to the three-necked flask and heat the water bath to 98 °C. Continue the reaction at this temperature for 30 min after the water is added. After removing the water bath, transfer the solution to a 1000 mL beaker and slowly add 400 mL of deionized water and 10 mL of hydrogen peroxide. Continue stirring the reaction for 1 h. (26) The reaction solution was poured into a centrifuge tube and centrifuged for 5 min. After the supernatant was discarded, the solution was centrifuged several times at the same speed using a 7% hydrochloric acid solution to remove metal ions and sulfate ions in the solution. After washing, a barium chloride solution was used to detect whether all sulfate ions were removed. The sample was then washed several times with deionized water until the pH was 6.95-7.
05. Finally, the clean sample was poured into an evaporating dish and placed in a freeze dryer for drying. After drying, it was ground into powder using a grinder.
8. The use of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 4, characterized in that: The filler layer includes nano zero-valent iron loaded graphene oxide, which is prepared by the following method: The prepared nano zero-valent iron and graphene oxide were ground in a mortar in a mass ratio of 1:1, and a certain amount of anhydrous ethanol and polyvinyl pyrrolidone dispersant were added. The mixture was broken into a sol and recombined by ultrasound for 10 min. After adjusting the pH, the reaction was carried out for a period of time. After the reaction was completed, it was transferred to a vacuum drying oven and dried for 12 h to obtain nano zero-valent iron loaded graphene oxide.
9. The use of a five-in-one composite sulfur autotrophic denitrification filter material according to claim 4, characterized in that: The filler layer includes biogas residue activated carbon, which is prepared by the following method: Using kitchen biogas residue as raw material, the biogas residue is filtered, dried and crushed into uniform powder; the powdered biogas residue is placed in a porcelain boat and pushed into a pyrolysis steel tube furnace of a tubular resistance furnace, and after nitrogen is introduced, the reaction is kept at a pyrolysis temperature of 1000℃ for 5 h; after the program is completed, the high-temperature resistant porcelain boat is taken out after naturally cooling to room temperature, and the black powder is collected to obtain biogas residue activated carbon with graphene structure.
Citation Information
Cited By
Synchronous nitrogen and phosphorus removal sewage treatment method and device
CN120774564A
Method for preparing composite sulfur autotrophic denitrification filler based on biodegradable micro-plastic and rapidly starting denitrification process
CN121020823A
